The effect of transformational leadership on employees’ performance in Malaysia’s public sector - Aminah Ahmad; Sylvia Nabila Azwa Ambad; Syed Jamal Abdul Nasir Syed Mohd; Nelson Lajuni (Human Resource Management Academic Research Society, 2020)
Employee performance is one of the main management topics that received substantial attention from scholars and practitioners. Thus, this study aims to investigate the effect of transformational leadership on employees’ performance in Malaysia’s public sector. A total of 286 sets of questionnaires are manually collected from a public sector department. The data are then analyzed by utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.3.2. This study found that transformational leadership has a significant positive influence on employee performance in Malaysia public service sector. This paper contributes to the body of knowledge on management literature by developing and empirically testing a causal model of transformational leadership on employee performance in the context of Malaysia’s public sector. The findings also suggest the importance of leadership styles that focuses on improving employees’ development, process-oriented, a commitment based on trust and expectations, which motivate employees to perform beyond expectation.